2021
DOI: 10.18087/cardio.2021.8.n1556
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte membranes beta-adrenoreactivity changes after renal denervation in patients with resistant hypertension, relationship with antihypertensive and cardioprotective intervention efficacy

Abstract: Aim      To study the functional condition of sympathoadrenal system as evaluated by beta-adrenoreactivity of erythrocyte membranes (beta-ARM) during two years following renal denervation (RD) in patients with resistant arterial hypertension (RAH) and to determine the relationship of this index with long-term antihypertensive and cardioprotective effectivity of this invasive treatment.Material and methods  The study included 48 patients (mean age, 57.2±8.7 years, 18 men) with RAH on a stable antihypertensive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 16 publications
0
1
0
2
Order By: Relevance
“…Thus, in one of the studies it has been found that patients with high risk of cardiac complications have the EMA highest values. 15 In this study has been shown that the EMA express determination can be used as one of the criteria for the risk of adverse cardiovascular events in cardiac patients.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, in one of the studies it has been found that patients with high risk of cardiac complications have the EMA highest values. 15 In this study has been shown that the EMA express determination can be used as one of the criteria for the risk of adverse cardiovascular events in cardiac patients.…”
Section: Discussionmentioning
confidence: 96%
“…Связывание соответствующих лигандов с этими рецепторами способно влиять на свойства эритроцитов (осмотическую резистентность, скорость агглютинации и др.) [39,40].…”
Section: Discussionunclassified
“…Преимуществом данного метода, определяющим его доступность для реальной клинической практики, является простота использования, высокая информативность и низкая стоимость расходных материалов. В настоящее время накоплены данные об особенностях β-АРМэ у больных после инфаркта миокарда (ИМ) [8][9][10], у пациентов с хронической сердечной недостаточностью (СН) [11], а также у больных РАГ [12]. Тем не менее сведения о степени выраженности симпатической гиперактивации на основе β-АРМэ в селективной группе больных с рфАГ как крайнего фенотипа неконтролируемой АГ до настоящего времени отсутствуют.…”
Section: Beta-adrenergic Reactivity Of Erythrocyte Membranes In Vario...unclassified